Economic and Social Cohesion in the EU: a critical approach - Juan R. Cuadrado-Roura; Rubén Garrido-Yserte; Miguel Ángel Marcos-Calvo (European Regional Science Association (ERSA), 2004)
Economic and Social Cohesion is one of the principal aims of European Union according to the Treaty. Although it has a clear and rather well defined political dimension, there is not a unique definition that permits a technical definition. Has an increase of Economic and Social Cohesion been observed in recent decades? How could this be measured? To answer these two questions it is necessary to define, first, what is the acceptable degree of regional inequalities and, second, which could be the variables or indexes to measure it properly (not only GDP per capita). The aim of this paper is to propose new answers to the problem, using REGIO database and applying multicriteria methods. We have researched a new empirical approach to the European Cohesion and we have calculated the accomplishment of a higher Economic and Social Cohesion between the European regions. The period analysed is 1987-1999 and the results are rather shocking and suggestive, particularly compared to the ones arising from the most conventional analysis on the evolution of GDP per capita. Key words: Social and Economic Cohesion; Regional Convergence; EU Regional Policy, multicriteria methods.
Keywords: 330; Social and Economic Cohesion; Regional Convergence; EU Regional Policy; multicriteria methods